2020
DOI: 10.1021/acsomega.0c00680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elicitation on Polyphenol and Carotenoid Metabolism in Butterhead Lettuce (Lactuca sativa var. capitata)

Abstract: The effect of elicitation in butterhead lettuce on carotenoid and polyphenol metabolism was evaluated. Different concentrations of arachidonic acid (AA), salicylic acid (SA), methyl jasmonate (MJ) (15, 45, and 90 μM) and Harpin protein (HP) (30, 60, and 120 mg/L) were applied on red and green butterhead lettuces. Total phenolic and flavonoid content were incremented by MJ (90 μM) in green and red lettuce. Carotenoids were increased in red lettuce (AA; 45 μM). Green lettuce modifies their phenolic acid profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…However, anthocyanin and flavonol contents increased significantly in BS-treated leaves compared to ASM-treated leaves. These results suggested that ASM did not promote the synthesis of flavonols such as quercetin and derivatives, or that other molecules (flavanols) such as catechin and derivatives were less well-detected at the wavelength used with the Dualex clip (480 nm) (Dr. Cluzet S. personal communication), or even that as yet unknown post-transcriptional phenomena might limit the biosynthesis to promote another pathway. A recent study comparing the effects of various elicitors on lettuce confirmed the role of SA in favor of flavanol biosynthesis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, anthocyanin and flavonol contents increased significantly in BS-treated leaves compared to ASM-treated leaves. These results suggested that ASM did not promote the synthesis of flavonols such as quercetin and derivatives, or that other molecules (flavanols) such as catechin and derivatives were less well-detected at the wavelength used with the Dualex clip (480 nm) (Dr. Cluzet S. personal communication), or even that as yet unknown post-transcriptional phenomena might limit the biosynthesis to promote another pathway. A recent study comparing the effects of various elicitors on lettuce confirmed the role of SA in favor of flavanol biosynthesis .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that ASM did not promote the synthesis of flavonols such as quercetin and derivatives, or that other molecules (flavanols) such as catechin and derivatives were less well-detected at the wavelength used with the Dualex clip (480 nm) (Dr. Cluzet S. personal communication), or even that as yet unknown post-transcriptional phenomena might limit the biosynthesis to promote another pathway. A recent study comparing the effects of various elicitors on lettuce confirmed the role of SA in favor of flavanol biosynthesis . Concerning the biosynthesis of phenylpropanoids, it was surprising to observe no overexpression of VvPAL and VvSTS in ASM-treated leaves, suggesting that VvSTS was probably already overexpressed in the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were, however, able to detect higher levels of defense-associated metabolites in both leaf and root tissues, such as SA. Furthermore, SA is known to increase flavonoid production in lettuce ( Moreno-Escamilla et al., 2020 ). This finding is congruent with our results of the flavonoid pathway being upregulated in the roots, higher flavonoid levels in the leaves within the first two weeks and higher levels of SA upon chitin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Bahkan elisitor sodium selenat tidak menunjukkan perbedaan yang signifikan dengan kontrol (Barrientos Carvacho et al, 2014). Elisitor pada konsentrasi tinggi dapat menginduksi akumulasi ROS yang lebih tinggi sehingga menyebabkan kematian sel yang dapat mengakibatkan penurunan fitokimia (Moreno-Escamilla et al, 2020). Pada penelitian ini kitosan 125 mg/L diduga menurunkan ketahanan sel tunas in vitro hasil regenerasi eksplan nodus yang berasal dari Pamekasan (A5) dan berpengaruh terhadap kemampuan sintesis dan akumulasi senyawa withanolid.…”
Section: Senyawa Withanolid Pada Tunas In Vitro Tanpa Perlakuan Elisi...unclassified